2013
DOI: 10.1111/acps.12108
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis‐inducing effects of cannabis are related to both childhood abuse and COMT genotypes

Abstract: Objective To test whether the association between childhood abuse, cannabis use and psychotic experiences (PEs) was moderated by the COMT (catechol‐O‐methyltransferase) gene. Method Psychotic experiences (PEs), childhood abuse, cannabis use and COMT Val158Met genotypes were assessed in 533 individuals from the general population. Data were analysed hierarchically by means of multiple linear regression models. Results Childhood abuse showed a significant main effect on both positive (β = 0.09; SE = 0.04; P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 52 publications
2
58
0
1
Order By: Relevance
“…COMT remains an interesting candidate gene for gene‐environment interactions in psychosis since it modulates dopamine function, is dynamically regulated and its expression alters with environmental stimuli (Tunbridge, 2010). In psychosis, the Val/Val rs4680 genotype may predispose individuals to stress‐related mesolimbic hyperactivity (Ira et al., 2014) and is known to increase the vulnerability to psychosis after cannabis use in those exposed to childhood abuse (Alemany et al., 2014). rs4680 has also been reported to moderate the effect of stress in induction of psychotic symptoms in a study of army recruits (Stefanis et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…COMT remains an interesting candidate gene for gene‐environment interactions in psychosis since it modulates dopamine function, is dynamically regulated and its expression alters with environmental stimuli (Tunbridge, 2010). In psychosis, the Val/Val rs4680 genotype may predispose individuals to stress‐related mesolimbic hyperactivity (Ira et al., 2014) and is known to increase the vulnerability to psychosis after cannabis use in those exposed to childhood abuse (Alemany et al., 2014). rs4680 has also been reported to moderate the effect of stress in induction of psychotic symptoms in a study of army recruits (Stefanis et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Yaygınlık için yanıtlar 0 (hiçbir zaman, bazen) ve 1 (sıklıkla, neredeyse sürekli) olarak yeniden kodlanmaktadır (Stefanis ve ark. 2002, Alemany ve ark. 2014).…”
Section: Toplumda Psişik Yaşantılar öLçeğiunclassified
“…Another population registry-based study found that family history of schizophrenia increased both the risk of schizophrenia and of acute cannabis-induced psychosis [25]. A history of child abuse (including sexual, physical, and/or emotional abuse) or neglect also increases the risk of developing schizophrenia after cannabis use [26][27][28][29][30][31]. Two large, population-based, longitudinal studies, in Greece and the Netherlands, both replicated findings that childhood maltreatment and cannabis use precede and are independently associated with increased risk of later psychosis, and that the combination of the 2 risk factors is synergistically associated with an increased risk of psychosis [28].…”
Section: Vulnerability Factorsmentioning
confidence: 99%
“…Two studies found a 3-way interaction between the COMT SNP, cannabis use, and a history of child abuse. Carriers of the COMT Val/Val genotype who were exposed to both childhood abuse and cannabis had more severe psychotic symptoms, whereas amongst carriers of a Met allele, childhood abuse was associated with more severe psychotic symptoms in noncannabis users [26,27]. AKT1 encodes for a protein kinase involved in second messenger transduction at the CB 1 R, and has also been implicated in increasing the risk for psychosis in cannabis users.…”
Section: Gene-by-environment Interactionsmentioning
confidence: 99%